A workshop on Doing Development Differently - CID (CID at Harvard University)
October 22-23, 2014 A workshop on Doing Development Differently Harvar d Kennedy School, Cambridge, MA Hosted by the Building State Capabilit y (BSC) program at the Center for International Development at Harvard University, and the Overseas Development Institute (ODI) with funding from the Governance Partnership Facility.